Fracionamento químico biomonitorado da fração aquosa do extrato etanólico das folhas de Cissampelos sympodialis eichl (milona) - Gomes , Ayala Nara Pereira (2015)
The use of natural products as a therapeutic resource is both ancient and ubiquotous. The species Cissampelos sympodialis (Menispermaceae) is popularly known as milona, jarrinha, abuteira and orelha-de-onça and the aqueous fraction of the ethanol extract of its leaves (FAEEF) has shown promising pharmacological actions. The Menispermaceae family is known by the presence of alkaloids and studies with C. sympodialis have shown that in addition to alkaloids, there is a significant amount of phenolic compounds. Although all pharmacological studies have been conducted with the FAEEF, chemical studies have focused so far in the ethanol extract of leaves and roots. Thus, the aim of this work was to conduct a bioassay-guided fractionation of FAEEF. The aqueous fraction was prepared using ultrasound-assisted extraction and then submitted to solid phase extraction (using reverse phase C18 cartridges). The cartridges were eluted using a gradient of MeOH:H2O yielding four fractions. The content of phenolics and total flavonoids in the fractions was determined using the Folin-Ciocalteau and Aluminium chloride methods respectively. The antioxidant potential of the fractions was determined using the iDPPH and ABTS radical methods.. All fractions were then submitted to immunopharmacological assays to evaluate the toxicity of the fractions to peritoneal murine macrophages (using the MTT viability assay), nitric oxide production (through nitrite quantification), and secretion of cytokines TNF-α and IL-1β using ELISA. The more polar fractions (eluted with 25% and 50% MeOH) had a hogher content of total phenolics (11.51 ± 1.73 and 14.50 ± 5.25 mg GAE/ 100 mg respectively) and also a higher antioxidante activity with the 25% fraction showing a EC50 of 13.54 ± 0.13 μg/mL using the ABTS method and 15.09 ± 0.14 μg/mL using the DPPH method. The fractions studied (at concentrations of 3 and 50 μg/mL did not presente toxicity tom urine macrophages and the 75% fraction was the only one that was able to significantly reduce the levels of NO, TNF-α and IL-1β, and thus is the fraction showing the most promising anti-inflammatory action. This study confirms the anti-inflammatory action of the species, besides demonstrating its antioxidant potential, and points to the role of polar substances, possibly as phenolic compounds responsible for these activities.